A widespread single amino acid mutation in AcrA reduces tigecycline susceptibility in Klebsiella pneumoniae - Yingchao Xu; Wenjia Wang; Wenya Su; Mingyu Wang; Hai Xu; Xuhua Zhang; Ling Li (Microbiology Spectrum, 2024)
ABSTRACT Whole-genome sequencing of a clinical tigecycline non-susceptible Klebsiella pneumoniae strain reveals a novel T188A mutation in AcrA, raising awareness on its role in tigecycline resistance. Through structural analysis of AcrAB-TolC in Escherichia coli that is highly homologous to K. pneumoniae AcrAB-TolC, weaker hydrogen-bond interaction of the AcrAA188 with lipoyl domain than AcrAT188 was found, which may provide greater flexibility for substrate translocation. In order to explore the resistance mechanism of this mutation, wildtype and T188A mutant of acrA were cloned in pACYC184 and transformed into acrA deleted K. pneumoniae. Several experiments, including measurement of MICs for tigecycline, survival assays, and determination of intracellular tigecycline content, were performed and suggested that T188A mutation in AcrA led to increased tigecycline MIC, improved strain survival under tigecycline stress, and decreased intracellular tigecycline concentrations. Further examination of prevalence of this mutation showed its surprisingly wide presence, particularly in hypervirulent multidrug-resistant K. pneumoniae sequence types. These results support the role of T188A as a widespread AcrA mutation reducing tigecycline susceptibility in K. pneumoniae through increasing tigecycline efflux and improving tigecycline tolerance. IMPORTANCE Tigecycline, a glycecycline antibiotic with broad-spectrum activity against almost all Gram-positive and Gram-negative bacteria, is a highly concerned “last-resort” antibiotic. In addition to plasmid-hosted mobile tet(X) conferring high-level resistance to tigecycline, there are many reports suggesting increased expression of AcrAB-TolC efflux pump leads to tigecycline non-susceptibility. However, the role of mutations in AcrAB-TolC on tigecycline resistance has not been identified. This study reports a novel T188A mutation of the AcrA subunit of AcrAB-TolC complex in a clinical tigecycline-resistant Klebsiella pneumoniae strain and reveals the role of AcrA mutation on tigecycline resistance in K. pneumoniae. High prevalence of A188 type AcrA in hypervirulent multidrug-resistant K. pneumoniae indicates that mutations of the AcrAB-TolC complex may play a larger role in determining bacterial pathogenesis and antibiotic susceptibility than previously expected.